2020
DOI: 10.1002/jor.24767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tamoxifen on tendon homeostasis and healing: Considerations for the use of tamoxifen‐inducible mouse models

Abstract: The use of tamoxifen‐inducible models of Cre recombinase in the tendon field is rapidly expanding, resulting in an enhanced understanding of tendon homeostasis and healing. However, the effects of tamoxifen on the tendon are not well‐defined, which is particularly problematic given that tamoxifen can have both profibrotic and antifibrotic effects in a tissue‐specific manner. Therefore, in the present study, we examined the effects of tamoxifen on tendon homeostasis and healing in male and female C57Bl/6J mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Of note, Cre activity was reported in the tendons or paratenon of several Cre lines, including S100a4, (253) α-Sma, (25,26) Gdf5, (45,120,122) Sox9, (76,78) Prx1, (45) Pgr4, (25,120) Acan, (25) Gli1, (45) Col1, (130,133) Col2, (45,101,110,113) OC, (139) Ctsk, (32) and Wnt1-Cre (81) lines, and administration of tamoxifen in female, but not male, mice can significantly impair tendon homeostasis. (254) Tendons are surrounded by an elastic connective tissue known as the paratenon, marked by the expression of tubulin polymerization-promoting protein family member 3 (Tppp3). (255) The Tppp3P2A-iCreER T2-T2A-eGFP and Tppp3 P2A-ER T2 CreER T2 lines have been shown to express Cre recombinase in the paratenon with minimal expression in the tendon midsubstance, and can be used to target Tppp3-positive cell populations, which harbor tendon stem/progenitor cells.…”
Section: Cre Mice Targeting Tendons and Ligamentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, Cre activity was reported in the tendons or paratenon of several Cre lines, including S100a4, (253) α-Sma, (25,26) Gdf5, (45,120,122) Sox9, (76,78) Prx1, (45) Pgr4, (25,120) Acan, (25) Gli1, (45) Col1, (130,133) Col2, (45,101,110,113) OC, (139) Ctsk, (32) and Wnt1-Cre (81) lines, and administration of tamoxifen in female, but not male, mice can significantly impair tendon homeostasis. (254) Tendons are surrounded by an elastic connective tissue known as the paratenon, marked by the expression of tubulin polymerization-promoting protein family member 3 (Tppp3). (255) The Tppp3P2A-iCreER T2-T2A-eGFP and Tppp3 P2A-ER T2 CreER T2 lines have been shown to express Cre recombinase in the paratenon with minimal expression in the tendon midsubstance, and can be used to target Tppp3-positive cell populations, which harbor tendon stem/progenitor cells.…”
Section: Cre Mice Targeting Tendons and Ligamentsmentioning
confidence: 99%
“…Of note, Cre activity was reported in the tendons or paratenon of several Cre lines, including S100a4 , ( 253 ) α‐Sma , ( 25,26 ) Gdf5 , ( 45,120,122 ) Sox9 , ( 76,78 ) Prx1 , ( 45 ) Pgr4 , ( 25,120 ) Acan , ( 25 ) Gli1 , ( 45 ) Col1 , ( 130,133 ) Col2 , ( 45,101,110,113 ) OC , ( 139 ) Ctsk , ( 32 ) and Wnt1‐Cre ( 81 ) lines, and administration of tamoxifen in female, but not male, mice can significantly impair tendon homeostasis. ( 254 )…”
Section: Cre Mice Targeting Tendons and Ligamentsmentioning
confidence: 99%
“…Tamoxifen (10–20 mg twice per day) has a longer history of use than rituximab as an additional drug to corticoids; it may be added to them or even offered as a single medication. This selective estrogen receptor modulator is beneficial not through its anti-estrogen capacity but via anti-fibrotic effects by stimulating transforming growth factor (TGF- β ), a cytokine released by fibroblasts and epithelial cells acting as a growth inhibitor of various cells (including fibroblasts) [ 12 , 13 ]. The need for anti-fibrotic effects also indicates mycophenolate mofetil (1 g twice per day) which is approved for systemic fibrosis, but it has limited applications due to severe side effects (pancytopenia or renal function damage) [ 2 , 6 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have also reported differential effects of tamoxifen treatment before animal injury models in males compared with females. 22–25 While the current study was not powered to evaluate sex differences in response to tamoxifen, this will be an important consideration for future analyses.…”
Section: Discussionmentioning
confidence: 99%